English Cultural Terminologies in Tourism of North Sumatera Brochures : Translation Studies - Mayasari, Misla Geubrina, Muhammad Ichsan Arrahman, (Invention: Journal Research and Education Studies, 2023)
This research aimed to describe the cultural terms used in tourism brochure in north sumatera. This research is motivated by the researcher’s interest because the researcher wants to find out what are the cultural terms that can be found in tourism brochure in north sumatera so that th researcher can atudying and learn the meaning of each word that is found in tourism brochure. There are 30 data that the researcher has pick. From the 30 data, there are 15 data contain communicative translation, 9 data contain free translation, 4 data contain adaptive translation, and 2 data contain idiomatic translation. This research used qualitative methods and the purpose of this research is to understanding the meaning of each cultural terms that is found in the tourism brochure.